Preserved boreal zone forest massif mass estimation during fire extinguishing by liquid aerosol; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Shlegel N. E. Nikita Evgenjevich (2017, 2017)
Title screen